2022
DOI: 10.3390/pharmaceutics14051100
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancerous Potential of Polysaccharides Derived from Wheat Cell Culture

Abstract: There is a global need to discover effective anti-cancerous compounds from natural sources. Cultivated wheat cells can be a valuable source of non-toxic or low toxic plant-derived polysaccharides. In this study, we evaluated the anti-cancer ability of seven fractions of wheat cell culture polysaccharides (WCCPSs) in the HCT-116 colon cancer cell line. Almost all (6/7) fractions had an inhibitory effect on the proliferation of colon cancer cells, and two fractions (A-b and A-f) had considerable therapeutic inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…The production of EPS through plant cell suspension culture that can be retrieved from the growth medium is common [ 15 , 21 , 37 , 38 ]. The EPS produced can be categorized based on their major molecular structures such as glucans, galacturonan, and xyloglucan.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of EPS through plant cell suspension culture that can be retrieved from the growth medium is common [ 15 , 21 , 37 , 38 ]. The EPS produced can be categorized based on their major molecular structures such as glucans, galacturonan, and xyloglucan.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite kenaf’s encouraging performance within the therapeutic field, most of the reported activities are still heavily dependent on harvesting the physical crop itself which indirectly translates into our total reliance on traditional farming to retrieve kenaf valuable extracts. In the long run, this practice is deemed to be unsustainable as the end-products quality and efficiency could vary due to inconsistent farming practices, unpredictable climatic conditions, and pest infestation [ 15–17 ]. Besides, land availability will become an issue as well for the mass production of kenaf solely for its therapeutic potential as the farmers may have to compete with other crop growers, especially for food and staple crops [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, natural polysaccharides have attracted the attention of researchers due to their safety and biological activity [9]. Studies have reported that polysaccharides extracted from TCM have few adverse effects and various biological functions on cancer [10], hyperlipidemia [11], inflammation [12], immunity [13], and antioxidation [14]. Polysaccharides from Penthorum chinense Pursh have been shown to inhibit H22 cell growth via the induction of a mitochondrial-dependent apoptosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…WB contains high-value health-promoting components, including dietary fibre and phenolic compounds [ 9 ]. There is in vivo and in vitro evidence that WB polysaccharides are antitumour agents with immunomodulatory activity [ 10 , 11 ]. WB polysaccharides activate cells of the innate immune system (macrophages), stimulating the secretion of pro-inflammatory cytokines and the production of ROS via toll-like receptor 4-p38 MAPK [ 12 ] and NF-κB signalling pathways [ 13 ].…”
Section: Introductionmentioning
confidence: 99%